Organisational trust, commitment and turnover intention in employees of domestic and foreign banks in Ghana - Thomas Addae Nketsiah; Emmanuel Anokye Nkansah (Cogent Business & Management, 2024)
The study examined the relationship between organisational trust, organisational commitment and turnover intention among employees of banks in Ghana. Participants were drawn from both domestic banks and foreign-owned banks. A cross-sectional research design was adopted for this study and a sample of 128 participants was conveniently selected for the study. A set of questionnaires measuring organisational trust, organisational commitment and turnover intention were administered to the participants. Analysis of the data revealed a significant negative relationship between organisational trust and turnover intention. Also, a significant negative relationship between organisational commitment and turnover intention was observed. Organisational commitment was identified as the only significant predictor of turnover intention and accounted for 43.6% of the variance in turnover intention. Further analysis showed that the affective component (β = −.374, p < .001) accounted for the most strength in reducing turnover intention than the continuance (β = −.246, p < .01) and normative components (β = −.245, p < .001). Organisational commitment was found to be significantly higher in foreign banks than in domestic banks. The turnover intention was significantly higher in domestic banks than in foreign banks. Concerning organisational trust, no significant difference was observed between domestic and foreign banks. Relevant stakeholders in the banking sector need to pay attention to the significant roles of organisational trust and organisational commitment in mitigating the turnover intentions of their employees.